Solution of Linear and Quadratic Equations Based on Triangular Linear Diophantine Fuzzy Numbers. (27th October 2021) - Khan, Naveed; Yaqoob, Naveed; Shams, Mudassir; Gaba, Yaé Ulrich; Riaz, Muhammad
Abstract : This paper is introducing a new concept of triangular linear Diophantine fuzzy numbers (TLDFNs) in a generic way. We first introduce the concept of TLDFNs and then study the arithmetic operations on these numbers. We find a method for the ranking of these TLDFNs. At the end, we formulate the linear and quadratic equations of the types A + X = B, A · X + B = C, and A · X 2 + B · X + C = D where the elements A, B, C, and D are TLDFNs. We provide a procedure for the solution of these equations using s, t, u, v -cut and also provide the examples.